The CO2CRC Otway Shallow CO2 Controlled Release Experiment: Site Suitability Assessment. (July 2017) - Feitz, A.J.; Pevzner, R.; Harris, B.; Schaa, R.; Tertyshnikov, K.; Ziramov, S.; Gunning, M.; Ransley, T.R.; Lai, E.; Bailey, A.H.; Schacht, U.; Fomin, T.; et al.
Abstract: The CO2CRC is undertaking a feasibility study for a planned controlled release and monitoring experiment at a shallow fault at the CO2CRC Otway Project site in 2018. Interpretation of pre-2016 seismic data could trace the height of the fault to approximately 100 m below the ground surface, at which point the resolution of the existing seismic data was insufficient to delineate the fault any further. To better understand the shallow geology at the Otway Project site and to map the extent of the shallow fault, new geophysical surveys were acquired over the Otway site during 2016. This included a high resolution, shallow focused, 3D seismic survey to provide greater delineation of the newly identified fault in the Port Campbell Limestone on the Otway Project site, and a high resolution resistivity survey to map the vertical extent of the fault towards the ground surface. Aerial imagery and LIDAR data were also collected. The seismic survey data exhibit greatly improved vertical and lateral resolution compared to previous seismic surveys. Preliminary pre-stack time migration (PreSTM) processing of the data show that the target fault can be clearly imaged at 30 ms TWT and the fault tip can be mapped to within approximately 25 m of the surface. Approximately 5 m of throw is identified at approximately 140 m depth and the throw appears to decrease in magnitude as the fault extends towards the surface. This, plus an identified dip angle of ∼70° (east), suggests that it is most likely a normal fault. There is no evidence of topographical features associated with the surface expression of the shallow fault using LIDAR and aerial imagery. Electrical Resistivity Imaging (ERI) results indicate that there are 3 distinct layers in the shallow geology of the Otway site, including a higher resistivity, more clay influenced, 3-5 m thick layer at the surface. The resistivity is also surprisingly heterogeneous over the site, suggesting that the shallow geology is complex. Preliminary hydraulic conductivity measurements confirm that the Port Campbell Limestone is highly permeable in the vicinity of the Otway Project site. The target fault at the CO2CRC Otway Project site appears to be a suitable candidate for a shallow CO2 injection experiment.